2022
DOI: 10.3390/vaccines10030459
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron Symptomatic Infections in Previously Infected or Vaccinated South African Healthcare Workers

Abstract: We investigated Omicron infections among healthcare workers (HCW) presenting with symptoms of SARS-CoV-2 infection and evaluated the protective effect of vaccination or prior infection. Between 24 November and 31 December 2021, HCW in Johannesburg, South Africa, were tested for SARS-CoV-2 infection by Nucleic Acid Amplification Test (NAAT). Blood samples collected either at the symptomatic visit or in the 3 months prior, were tested for spike protein immunoglobulin G (IgG). Overall, 433 symptomatic HCW were in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 17 publications
0
33
3
Order By: Relevance
“…These results are consistent with self-reported symptom data during the BA.1 wave from the ZOE study, a large smartphone app-based community study in the UK and are supportive of the expansion of cardinal symptoms by the NHS in its COVID-19 guidance issued in April 2022 (13,15). Despite analyses of hospitalisation and mortality data indicating that Omicron caused lesssevere clinical disease (7,8,10), our data suggests that COVID-19 continues to cause a significant symptom burden in non-hospitalised adults with COVID-19, with attendant impacts on healthcare resources, and incidence of post-COVID syndrome (PCS) (11,12). This continued burden is well-illustrated by the shift in the numbers of asymptomatic cases we .…”
Section: Discussionmentioning
confidence: 69%
“…These results are consistent with self-reported symptom data during the BA.1 wave from the ZOE study, a large smartphone app-based community study in the UK and are supportive of the expansion of cardinal symptoms by the NHS in its COVID-19 guidance issued in April 2022 (13,15). Despite analyses of hospitalisation and mortality data indicating that Omicron caused lesssevere clinical disease (7,8,10), our data suggests that COVID-19 continues to cause a significant symptom burden in non-hospitalised adults with COVID-19, with attendant impacts on healthcare resources, and incidence of post-COVID syndrome (PCS) (11,12). This continued burden is well-illustrated by the shift in the numbers of asymptomatic cases we .…”
Section: Discussionmentioning
confidence: 69%
“…Most individuals infected with COVID-19 before are likely to be reinfected due to the increased immune escape capability of the Omicron variant, which may cause a higher percentage of asymptomatic infections [ 46 , 47 ]. Previous studies showed that the Omicron variant-positive individuals with booster doses of vaccines had a lower percentage of severe symptoms and a higher percentage of no symptoms or mild symptoms [ 48 , 49 ]. This suggests that the current vaccine is still effective in preventing severe cases but seems to be less effective in preventing Omicron infections.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant has overtaken the globe faster than any previous SARS-CoV-2 variant 20 . Its increased fitness appears linked, at least in part, to its extensive antibody evasion properties and ability to cause vaccine breakthrough infections 21 and reinfections 5 . Initially, most Omicron cases were caused by BA.1, but the BA.2 variant appears to have a higher growth rate in most populations and is replacing BA.1 as the dominant variant in many locations 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Breakthrough infection following SARS-CoV-2 vaccination has been observed since the rollout of vaccines 1,2 and has been associated with specific variants including Beta 3 , Delta 4 , and Omicron 5 . The predisposing factors to breakthrough infection and the consequences of breakthrough infection for SARS-CoV-2 immunity are poorly understood.…”
Section: Introductionmentioning
confidence: 99%